الأسر العلمية المغربية في الحجاز من خلال كتاب الضوء اللامع للسخاوي - البشير قشوط; بلقاسم معوش (University Of Eloued جامعة الوادي, 2026)
"شاهدت الحجاز خصوصا مكة المكرمة والمدينة المنورة خلال القرنين الثامن والتاسع الهجريين الرابع عشر والخامس عشر الميلاديين حضورا علميا مميزا لعدد من الأسر العلمية المغربية, التي أسهمت في الحياة العلمية الثقافية والدينية للمنطقة, ومن أهم المصادر التي توثق لهذا الحضور "" كتاب الضوء اللامع لأهل القرن التاسع "" لشمس الدين السخاوي )831-902ه/1428-1496م(, الذي رصد فيه سير عدد من علماء الأسر العلمية المغربية الذين استقروا في الحجاز طلبا للعلم ونشره وقد أشار السخاوي إلى أسماء عدة أسر مغربية علمية تميز أفرادها بالعلم والتفقه والتدريس, مما يؤكد أن الحضور المغربي في الحجاز خلال الفترة الوسيطية لم يكن عابرا بل كان مؤثرا, وأسهم في التواصل الثقافي بين المغرب والمشرق الإسلاميين, وقد عكس هذا التفاعل العلمي مدى ارتباط المنطقتين ببعضهما تلك الفترة." "During the eighth and ninth centuries AH (fourteenth and fifteenth centuries AD), the Hijaz, especially Mecca and Medina, witnessed a distinguished scholarly presence of a number of Maghreb scholarly families, who contributed to the scientific, cultural and religious life of the region. One of the most important sources documenting this presence is “The Shining Light of the People of the Ninth Century” by Shams al-Din al-Sakhawi (831-902 AH/1428-1496 AD), in which he monitored the biographies of a number of scholars from Maghreb scholarly families who settled in the Hijaz seeking knowledge and disseminating it, or residing in the holy places. Al-Sakhawi mentioned the names of several Maghreb scholarly families whose members were distinguished by knowledge, jurisprudence and teaching, which confirms that the Maghreb presence in the Hijaz during the medieval period was not fleeting, but rather influential, and contributed to the cultural communication between Maghreb and the Islamic East. This scholarly interaction reflected the extent of the connection between the two regions during that period."
مذكرة ماستر قسم علوم انسانية تخصص تاريخ الغرب الإسلامي في العصر الوسيط
Keywords: المغرب الإسلامي; المدينة المنورة; مكة; الحجاز; الأسر العلمية المغربية; Maghreb scientific families; Hijaz; Mecca; Medina; Islamic Maghreb